(untitled) (Academicia Globe: Inderscience Research, 2025)
In the article, the article in the article on the development of modern approaches, and leading and leading factors in the context of the development of vocational competitors of higher education institutions, the professional competence of heads and internal training, and the professional competence of the degree and agrological approaches The issues of improving the organizational and governance mechanisms of the development are covered and the development of the professional competence of the professional competence, and the practical introduction of didactic mechanisms based on innovative and interactive technologies.